Behavior patterns and career paths differentiation among Chinese international students in Japan: Insights from culture in action model - Jiao, Ran (Journal of Interdisciplinary Studies in Education, 2026)
This study investigates how cultural tools shape the career paths differentiation of Chinese international students in Japan, with particular focus on the behavior patterns that emerge in this process. Drawing on the culture in action model, the research adopts a constructivist epistemology and a hermeneutic methodological approach to analyze in-depth interviews. Findings reveal that family background and early experiences significantly influence students’ motivations and approaches to career planning. Moreover, the meaning of work, as constructed through individual values, plays a decisive role in guiding career choices. Two distinct behavior patterns are identified: a goal-driven pattern, in which students actively pursue predetermined objectives, and an opportunity-following pattern, in which students adapt to emerging prospects.